Proposed Algorithm for the Diagnosis and Management of Diabetic Gastroparesis in the Indian Clinical Setting - Mohan V. G. Prasad; Nitesh Pratap; Showkat Zargar; Ravi B. Shankar; Umesh Jalihal; Raj V. Venugopal (Indian Journal of Endocrinology and Metabolism)
Diabetic gastroparesis (DGP) is a microvascular complication of diabetes, characterised by delayed gastric emptying and cardinal symptoms such as nausea, vomiting, early satiety, post-meal discomfort, bloating, and appetite loss. Diagnosis relies on identifying these symptoms and excluding obstructions. India-specific DGP management algorithm was developed by 50 expert gastroenterologists across India. It offers a systematic approach tailored to Indian clinical settings, emphasising a comprehensive evaluation encompassing medical history, clinical examination, and laboratory investigations for diagnosing DGP. The management strategy involves glycemic control, dietary adjustments, prokinetics with antiemetics, and stepwise treatment modification if initial approaches prove ineffective. Additionally, the algorithm underscores the significance of endoscopic evaluation and gastric emptying studies in DGP diagnosis, as well as the use of prokinetics, antiemetics, and neuromodulators in treatment. Notably, the experts favoured itopride as the preferred and relatively safer prokinetic for treating DGP and its varied clinical presentations.